Iowa RBA, November 29-December 4, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Emails of Iowa RBA updates for November 29 to December 4, 1999. Highlights of the updates include sightings of Pomarine Jaeger, White-winged Crossbill, Surf Scoter, Pacific Loon, and a Yellow-billed Loon. Includes seven Iowa RBA update emails and two emails to the IA-BIRD list regarding a Varied Thrush and a Pacific Loon. Epson - sheet feed/flatbed